PATIENT HEALTH PROFILE DURING TAKING PREOPERATIVE MEDICATION WITHNOT TAKING SEDATION - Mustafa, Dr. Jindale; Trump, Dr. Lyndsey (International Journal of Multidisciplinary Research and Studies, 2021)
Some patients receive narcotic drugs. Patient health profile without administered any Analgesia, Meperidine, Sedatives during preoperative or premedication in suburbanization Hospital for Colonoscopy. Colonoscopy may be a standard and useful examination within the diagnosis of colorectal diseases; however, it always causes pain to patients